Pengembangan Bahan Ajar Fisika Berbasis Way of Investigating untuk Meningkatkan Keterampilan Proses Siswa SMK - Obimita Ika Permatasari; Demi Trisnawati (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
Process skills are very important in learning. Process skills can be approached by investigating a phenomenon. This research aims to develop way of investigating physics teaching materials to improve students' process skills. This study uses a Research and Development (RD) design. Data collection methods used are tests, observations, questionnaires, and documentation. The research sample was taken by purposive sampling. Based on data analysis, it is known that the teaching materials developed are categorized as very valid and suitable for use with an average value of 89.97. The readability of teaching materials is in the good category with a value of 77.88. The process skill gain test in the experimental class of 0.303 is in the medium category, while in the control class of 0.297 is in the low category. Student responses to the developed teaching materials are very good, with an average percentage of 86.65%. The results of this study indicate that way of investigating teaching materials are appropriate to be used in physics learning, especially to improve students' process skills.